Review of James Leach and Lee Wilson (eds.) Subversion, Conversion, Development: Cross-cultural Knowledge Ex- change and the Politics of Design (2014). Cambridge, MA: The MIT Press. ISBN: 9780262027168. (2017) - Kelly, Matthew
No abstract available